Epistemologi Harald Motzki dalam Kritik Hadis dan Relevansinya bagi Kajian Hukum Perkawinan Islam - Azizah, Aisyatul; Komarudin, Moh.; Aqilah, Farah (LPPM UNU BLITAR, 2025)
Hadith is the second primary source of Islamic law after the Qur'an and plays a vital role in shaping legal norms, including in matters of marriage law. However, certain hadiths used as legal foundations—particularly those concerning the age of marriage remain contested in terms of their validity and contextual relevance. In this regard, Harald Motzki’s methodological contributions are significant, especially through his isnād-cum-matn analysis and dating theory, which allow for a historical and textual tracing of hadith transmissions. This study employs a qualitative approach using library research to examine Motzki’s epistemology and its relevance to reinterpreting hadiths often used to justify child marriage practices. The findings suggest that Motzki’s approach reveals the dynamic nature of hadith transmission and opens the door for more contextual and just reinterpretations of Islamic law. Thus, Motzki’s epistemology is not only essential in the academic study of hadith but also strategically valuable in supporting the reconstruction of Islamic marriage law that aligns with child protection and the principles of maqāṣid al-sharī‘ah.